2021
DOI: 10.1177/07334648211005868
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Care, Fall Detection, and Ambient-Assisted Living Technologies Help Older Adults Age in Place: A Scoping Review

Abstract: Objectives: We aimed to describe recent technologic advances in the three domains of dementia care, falls, and home supports; summarize existing literature on usability; and identify knowledge gaps. Methods: A comprehensive search of five databases for recent peer-reviewed publications was conducted in May 2020. Independent reviewers performed title/abstract review, full-text screening, data extraction, and study characteristic summarization. Results: Out of 2,696 citations, 151 articles were retrieved for ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 71 publications
2
34
0
Order By: Relevance
“…As dementia is a neurodegenerative disease, people with dementia will eventually experience decline and require assistance to safely complete daily tasks. Technology and telehealth can help people with dementia age in place longer ( 12 , 13 ). Previous research supports our findings that older adults are generally not as interested in adopting and utilizing technology in their daily life ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…As dementia is a neurodegenerative disease, people with dementia will eventually experience decline and require assistance to safely complete daily tasks. Technology and telehealth can help people with dementia age in place longer ( 12 , 13 ). Previous research supports our findings that older adults are generally not as interested in adopting and utilizing technology in their daily life ( 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, however, a growing body of research has shifted attention to identify what functions are important from caregivers' perspective. A recent review article revealed that compared to older adults, caregivers prefer technologies with monitoring functions as these features could reduce their caregiving burden and bring them a greater sense of security (Gettel et al, 2021). Consistent with previous findings, our research suggests that caregivers would appreciate features that go beyond just reporting that a fall has taken place.…”
Section: Discussionmentioning
confidence: 99%
“…Although the innovation of these technologies is exciting and commendable, the translation from concept to use within aged care services has been slow and fragmented (Pilotto et al, 2018; Peine & Neven, 2019). Uptake of technology has been increasing over the last decade (Anderson & Perrin, 2017), but remains dependent on older adults’ usability of the technology (Gettel et al, 2021). To move beyond this, two key issues have been identified to better harness the potential of technologies used within aged care: (1) a more comprehensive understanding of end-users’ technology needs and preferences (Pilotto et al, 2018; Peine & Neven, 2019; Pruchno, 2019) and (2) greater synergistic and multidisciplinary working collaborations between specialists in gerontology and technology.…”
Section: Introductionmentioning
confidence: 99%